1992
DOI: 10.1152/ajpheart.1992.263.4.h1034
|View full text |Cite
|
Sign up to set email alerts
|

L-selectin function is required for beta 2-integrin-mediated neutrophil adhesion at physiological shear rates in vivo

Abstract: In vivo interactions between neutrophils and endothelial cells (EC) follow a multistep process involving two distinct neutrophil adhesion receptors. L-selectin, constitutively functional on resting neutrophils, mediates an activation-independent primary interaction resulting in rolling along the venular wall. Subsequent activation of rolling neutrophils induces upregulation and functional activation of beta 2-integrins (CD11/CD18) leading to firm attachment. Based on previous findings we hypothesized that, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
144
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 6 publications
10
144
0
1
Order By: Relevance
“…Similarly, Nonaka and colleagues (33) observed in a retinal ischemia-reperfusion model that the maximum number of rolling leukocytes can be significantly reduced by ischemic preconditioning. Finally, Wang and co-workers (40) showed that preconditioning with morphine increases shedding from the neutrophil surface of gp100 MEL14 , the murine analog to human L-selectin and a key adhesion molecule involved in the initial steps of leukocyte rolling (39). On the basis of our present observation, we speculate that, in analogy to these earlier reports, "inflammatory preconditioning" may play an important role in our studies.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Nonaka and colleagues (33) observed in a retinal ischemia-reperfusion model that the maximum number of rolling leukocytes can be significantly reduced by ischemic preconditioning. Finally, Wang and co-workers (40) showed that preconditioning with morphine increases shedding from the neutrophil surface of gp100 MEL14 , the murine analog to human L-selectin and a key adhesion molecule involved in the initial steps of leukocyte rolling (39). On the basis of our present observation, we speculate that, in analogy to these earlier reports, "inflammatory preconditioning" may play an important role in our studies.…”
Section: Discussionsupporting
confidence: 85%
“…migration in response to soluble gradients of chemoattractants) action (Rot, 1993), and, that endothelial cells have specific binding sites for this cytokine (Rot, 1992;Tanaka et al, 1993). According to this recently proposed model, the involvement of a co-factor(s) which facilitates leucocyte rolling on the endothelial wall (Rot, 1992), is a fundamental requisite for a subsequent firm adhesion via P2-integrins (Lawrence & Springer, 1991;Von Andrian et al, 1992). Previous studies have suggested that IL-8-induced PMN infiltration in the rat peritoneal cavity may require the presence of resident mast cells (Ribeiro et al, 1991), and that a genetic strain of mice deficient of this cell type have an impaired response to IL-8 (reported in Rot, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is involved in many physiological processes, including lymphocyte activation, adhesion, and proliferation (12). There is also increasing evidence that CD44 and L-selectin contribute to tumor metastasis (13,14).Under many physiologic conditions, L-selectin initiates the first step of the adhesion cascade (15,16). While surveying the vascular bed, rapidly flowing leukocytes face the challenge to establish contact to static ligands of the endothelial layer at high velocities.…”
mentioning
confidence: 99%
“…Under many physiologic conditions, L-selectin initiates the first step of the adhesion cascade (15,16). While surveying the vascular bed, rapidly flowing leukocytes face the challenge to establish contact to static ligands of the endothelial layer at high velocities.…”
mentioning
confidence: 99%